The implementation of aptitude treatment interaction to increase students’ learning activity and achievement in learning of the qur’an hadith in Madrasah Tsanawiyah - Jiyanto, Jiyanto; Widiani , Desti (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This research is a classroom action research that aims to increase student learning activities and achievement in the subjects of the Qur'an Hadith through the Aptitude Treatment Interaction (ATI) learning model in class VIII MTs N 6 Sragen. The data collection method used observation sheets for teacher activities, student activities, and tests to determine learning outcomes. This research was conducted in two cycles. The procedure of this research includes four stages: (1) planning, (2) implementing actions, (3) observation, (4) reflection. Data were collected by observing and testing for each cycle after being given treatment through the Aptitude Treatment Interaction (ATI) learning model. The data collected were analyzed using quantitative and qualitative analysis. The results of research cycle I and cycle II showed an increase in the student learning activity by 78% and 88%, respectively, and an increase in student achievement by 83% and 98%, respectively. The results of this study indicate that Aptitude Treatment Interaction (ATI) can be an alternative problem-solving in the classroom, especially for students who have low achievement in al-Qur'an hadith subjects.